CHELASI LOGAM BERAT TIMBAL PADA KEDELAI HITAM DENGAN MIKROKAPSUL ASAP CAIR - , ALDITA PRABANDARI, Prof. Dr. Ir. E. Purnama Darmadji, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The result of previous studies showed that the intensification of soybeans contained high content in lead (Pb). Intensification on agricultural crops, besides to increasing agricultural productivity, also leads to high accumulation of heavy metals in plants due to the use of chemical fertilizers and pesticides. One of them occurs in black soybean. This study was aimed to identify Pb contamination on the skin, cotyledon and whole black soybean, the effectiveness of the marinade ingredients and soaking time effect to the reduction of Pb levels in each part of black soybean. This work used immersion method with microcapsules of liquid smoke marinade ingredients and comparison with the variation of the concentration of citric acid 10% and 20% and soak time variations, 40 minutes, 80 minutes and 120 minutes. At each sample of whole seeds, cotyledons and skin was being analyzed the Pb content at each immersion treatment. Pb level analysis was done by Atomic Absorption Spectrophotometer (AAS) and the obtained data were analyzed with âonewayâ ANOVA with a significance level of Î± = 0.05%. Differentiation test was held using Duncan method. The results showed that black soybeans contaminated by Pb with detectable levels of 8.1713 ppm and was detected from skin to cotyledon soybean. Soybean cotyledon was contaminated with levels of 2.5563 ppm. Soybean skin was contaminated with levels of 2.3829 ppm. Concentration and time of immersion of the most influential in lowering the concentration of Pb is 20% and the immersion time of 120 minutes. Pb content of whole black soybean seed soaking liquid smoke results 20% for 120 minutes is 1.7088 ppm, the black soybean cotyledon at 0.6870 ppm, and on the skin of 0.4534 ppm black soybean. While the level of intact black soybean seed soaking results 20% citric acid for 120 minutes is 2.8986 ppm, the black soybean cotyledon is at 1.0885 ppm, and on the skin is of 0.7494 ppm black soybeans. Microcapsules of liquid smoke marinade ingredients more effective than citric acid in lowering levels of Pb.